(3‐Oxo‐[1, 2, 4]triazolidin‐1‐yl)bis (butane‐1‐sulfonic acid) functionalized magnetic γ‐Fe2O3 nanoparticles: A novel and heterogeneous nanocatalyst for one‐pot and efficient four‐component synthesis of novel spiro[indeno[1, 2‐b]quinoxaline derivatives. (18th March 2019) - Mohammadi, Hadi; Shaterian, Hamid Reza
Abstract : The efficient synthesis of novel spiro[indeno[1, 2‐ b ]quinoxaline derivatives via the four‐component condensation of amines, ninhydrin, isatoic anhydride, and о ‐phenylenediamine derivatives catalyzed by( 3‐oxo‐[1, 2, 4]triazolidin‐1‐yl)bis (butane‐1‐sulfonic acid) supported on γ‐Fe2 O3 as novel heterogenous magnetic nanocatalyst was described. The novel nanocatalyst was characterized by X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FT‐IR), vibrating sample magnetometry (VSM), Field Emission Scanning Electron Microscopy (FE‐SEM), and thermal analysis (TGA‐DTG). The nanoparticles covered by (3‐oxo‐[1, 2, 4]triazolidin‐1‐yl)bis (butane‐1‐sulfonic acid) showed enhanced catalytic performance in the preparation of spiro[indeno[1, 2‐ b ]quinoxaline derivatives in excellent yields. Moreover, this method showed several advantages such as mild conditions, high yields, easy work‐up, and being environmentally friendly. The catalyst can be easily separated from the reaction mixture by an external magnet, recycled, and reused several times without a noticeable decrease in catalytic activity. Abstract : The efficient synthesis of novel spiro[indeno[1, 2‐ b ]quinoxaline derivatives via the four‐component condensation of amines, ninhydrin, isatoic anhydride and о ‐phenylenediamine derivatives catalyzed by( 3‐Oxo‐[1, 2, 4]triazolidin‐1‐yl)bis (butane‐1‐sulfonic acid) supported on γ‐Fe2 O3 as novel heterogenous magnetic nanocatalyst was described. The novel nanocatalyst was characterized by several techniques and showed enhanced catalytic performance in preparation of spiro[indeno[1, 2‐ b ]quinoxaline derivatives in excellent yields.